2002
DOI: 10.2478/v100-50-008-79-x
|View full text |Cite
|
Sign up to set email alerts
|

Biometrical analysis of an urban population of the Blackbird (Turdus merula) in Szczecin in Poland

Abstract: Biometrical analysis of an urban population of the Blackbird (Turdus merula) in Szczecin in Poland In years 1996-2001, a biometrical investigation of an urban population of the Blackbird was conducted in two parks of Szczecin. Altogether, 388 birds were measured, including 191 females and 197 males. Adult females were bigger than young females (in all analysed parameters). Among males there were differences in wing, tail and total head lengths. In both sexes the strongest correlation occurred be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
2
26
1
2
Order By: Relevance
“…The reduced breeding success after divorce contradicts the predictions of a better option and the incompatibility hypothesis which assumes that the divorce is a strategy for an individual to increase its reproductive success (Choudhury 1995). However, the reduced breeding success may be a result of poor adaptation for the population studied to recently observed increase in predator pressure in city centers (Marchant et al 1990, Wysocki 2005b. In a city park with a very simple vegetation structure, the sites preferred by the Blackbird for the highest nest concealment (conifers) are often an ecological trap because they are selectively searched by corvids , Wysocki 2005c.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The reduced breeding success after divorce contradicts the predictions of a better option and the incompatibility hypothesis which assumes that the divorce is a strategy for an individual to increase its reproductive success (Choudhury 1995). However, the reduced breeding success may be a result of poor adaptation for the population studied to recently observed increase in predator pressure in city centers (Marchant et al 1990, Wysocki 2005b. In a city park with a very simple vegetation structure, the sites preferred by the Blackbird for the highest nest concealment (conifers) are often an ecological trap because they are selectively searched by corvids , Wysocki 2005c.…”
Section: Discussioncontrasting
confidence: 44%
“…An individual's age was determined from contrast in wing plumage (Svensson 1992). Because most of the birds were ringed as nestlings, fledglings, or in their second year of life, the exact age structure of the population studied is well known (Wysocki 2004a).…”
Section: Methodsmentioning
confidence: 99%
“…The populations of common blackbird (Turdus merula) in urban habitats and forests differ from one another in terms of genetics, breeding, characteristics, and ecological features (Snow, 1958;Batten, 1974;Luniak and Mulsow, 1988;Partecke et al, 2004;Wysocki, 2004b;Partecke et al, 2006). In the same vein, studies revealed that park populations have a higher rate of breeding success than forest populations, together with different types of nestsite selection and unique nest-site characteristics (Lovászi et al, 2000;Wysocki, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The role of testosterone has also been stressed in literature (Folstad & Karter, 1992, but see Roberts et al, 2004). Blackbirds are the only thrush species showing sexual dimorphism, but body size and weight of males and females are similar (Wysocki, 2002). Only females build nests but otherwise both sexes lead a similar lifestyle.…”
Section: Introductionmentioning
confidence: 99%